2018
DOI: 10.1007/s00429-018-1628-y
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion MRI-based cortical connectome reconstruction: dependency on tractography procedures and neuroanatomical characteristics

Abstract: Diffusion MRI (dMRI)-based tractography offers unique abilities to map whole-brain structural connections in human and animal brains. However, dMRI-based tractography indirectly measures white matter tracts, with suboptimal accuracy and reliability. Recently, sophisticated methods including constrained spherical deconvolution (CSD) and global tractography have been developed to improve tract reconstructions through modeling of more complex fiber orientations. Our study aimed to determine the accuracy of connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 69 publications
1
56
0
Order By: Relevance
“…While multiple studies have assessed test–retest reproducibility of white matter parcellations using cortical‐parcellation‐based strategies, for example, on the brain connectome network (Besson, Lopes, Leclerc, Derambure, & Tyvaert, ; Bonilha et al, ; Buchanan, Pernet, Gorgolewski, Storkey, & Bastin, ; Dennis et al, ; Duda, Cook, & Gee, ; Schumacher et al, ; Smith et al, ; Vaessen et al, ; Zhao et al, ; Zhang, Descoteaux, et al, ) and on anatomical fiber tracts (Besseling et al, ; Cousineau et al, ; Heiervang, Behrens, Mackay, Robson, & Johansen‐Berg, ; Kristo et al, ; Lin et al, ; Papinutto et al, ; Tensaouti, Lahlou, Clarisse, Lotterie, & Berry, ; Wang et al, ; Yendiki et al, ), there are no existing studies of fiber clustering, to our knowledge. Studies have suggested that fiber clustering approaches have advantages in parcellating the white matter in a highly consistent way, aiming to reconstruct fiber parcels/tracts corresponding to the white matter anatomy (Ge et al, ; Sydnor et al, ; Zhang et al, ; Zhang, Wu, Norton, et al, ; Ziyan, Sabuncu, Eric, Grimson, & Westin, ), while cortical‐parcellation‐based methods could be less consistent considering factors such as the variability of intersubject cortical anatomy, the dependence on registration between dMRI and structural images, and the presence of false positive/negative connections (Amunts et al, ; Fischl, Sereno, Tootell, & Dale, ; Maier‐Hein et al, ; Sinke et al, ; Zhang, Descoteaux, et al, ). However, to our knowledge, test–retest reproducibility of the cortical‐parcellation‐based and fiber clustering white matter parcellation strategies has not yet been quantitatively compared.…”
Section: Introductionmentioning
confidence: 99%
“…While multiple studies have assessed test–retest reproducibility of white matter parcellations using cortical‐parcellation‐based strategies, for example, on the brain connectome network (Besson, Lopes, Leclerc, Derambure, & Tyvaert, ; Bonilha et al, ; Buchanan, Pernet, Gorgolewski, Storkey, & Bastin, ; Dennis et al, ; Duda, Cook, & Gee, ; Schumacher et al, ; Smith et al, ; Vaessen et al, ; Zhao et al, ; Zhang, Descoteaux, et al, ) and on anatomical fiber tracts (Besseling et al, ; Cousineau et al, ; Heiervang, Behrens, Mackay, Robson, & Johansen‐Berg, ; Kristo et al, ; Lin et al, ; Papinutto et al, ; Tensaouti, Lahlou, Clarisse, Lotterie, & Berry, ; Wang et al, ; Yendiki et al, ), there are no existing studies of fiber clustering, to our knowledge. Studies have suggested that fiber clustering approaches have advantages in parcellating the white matter in a highly consistent way, aiming to reconstruct fiber parcels/tracts corresponding to the white matter anatomy (Ge et al, ; Sydnor et al, ; Zhang et al, ; Zhang, Wu, Norton, et al, ; Ziyan, Sabuncu, Eric, Grimson, & Westin, ), while cortical‐parcellation‐based methods could be less consistent considering factors such as the variability of intersubject cortical anatomy, the dependence on registration between dMRI and structural images, and the presence of false positive/negative connections (Amunts et al, ; Fischl, Sereno, Tootell, & Dale, ; Maier‐Hein et al, ; Sinke et al, ; Zhang, Descoteaux, et al, ). However, to our knowledge, test–retest reproducibility of the cortical‐parcellation‐based and fiber clustering white matter parcellation strategies has not yet been quantitatively compared.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of retrograde tracing, histological tracing also quantifies the number of axons in a projection, since each labeled projection neuron provides one axon. Studies performed in macaque (Azadbakht et al, 2015;Donahue et al, 2016;Schilling, Nath, et al, 2019;Zhang et al, 2018) , squirrel monkey (Gao et al, 2013; , pig (Knösche, Anwander, Liptrot, & Dyrby, 2015) , mouse (Calabrese, Badea, Cofer, Qi, & Johnson, 2015) and rat (Sinke et al, 2018) , have explored the relationship between tract-tracing experiments and tractography. Overall these studies have shown that diffusion MRI tractography provides a good estimate of structural brain connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Few explorations have been made on the ability of the different tractography approaches available to estimate structural connectivity weights (Gao et al, 2013) . Previous studies have mainly focused on the ability of tractography algorithms to properly estimate white-matter pathways by means of voxel-wise overlap (Knösche et al, 2015) , or on the detectability (presence or absence) of connections (Sinke et al, 2018) , or both Schilling, Nath, et al, 2019) .…”
Section: Introductionmentioning
confidence: 99%
“…This limitation makes it difficult to clearly establish the extent to which head motion is driving false-positive or false-negative connections. Previous studies examining the validity of different tractography algorithms have used synthetic DWI data where ground truth fibre bundles are known (Maier-Hein et al, 2017;Schilling, Daducci, et al, 2019;, or have relied on comparisons to axonal tract-tracing data (Sinke et al, 2018;Thomas et al, 2014). Simulations of head motion in a model where ground truths are known could allow for a more detailed characterisation of how streamline reconstructions are affected under such conditions, which in turn would allow for a better understanding of how preprocessing steps are or are not sensitive to residual motion-related artefacts.…”
Section: Limitationsmentioning
confidence: 99%